A Participation Model for Teaching English at Politeknik Negeri Media Kreatif - Hawa Asma Ul Husna; Ni Made Widiastuti; Iswandi Idris; Ramadani Ramadani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study dealt a participation model for teaching English at Politeknik Negeri Media Kreatif. It is used quantitative research design. The purpose of this study was to know how participation process in teaching, linguistic anthropology approach to research the phenomenon that cover speech and speech action. There were 40 students of Politeknik Negeri Media Kreatif as population and sample in this study. There were two instrument that conducted in this study, they were observation and questionnaire. The result of this study was the participation model of teaching English at Politeknik Negeri Media Kreatif should consider and focus on overcoming public speaking anxiety because they don't know how to start a conversation, public speaking anxiety because they can't predict what listeners expect, public speaking anxiety because Not ready to speak, public speaking anxiety is caused by not knowing what to do and still having concerns about the differences in the methods and materials taught by lecturers with material heard through audio devices or native English speakers.